Cartilage Imaging in Osteoarthritis - Alizai, Hamza; Walter, William; Khodarahmi, Iman; Burke, Christopher J. (Seminars in Musculoskeletal Radiology, 2019)
Osteoarthritis (OA) is the most common joint disease in the United States. The prevalence of OA is rising due to an aging population and increasing rates of obesity. Magnetic resonance imaging (MRI) allows an incomparable noninvasive assessment of all joint structures. Irreversible and progressive degradation of the articular cartilage remains the hallmark feature of OA. To date, attempts at developing disease-modifying drugs or biomechanical interventions for treating OA have proven unsuccessful. MRI-based cartilage imaging techniques have continued to advance, however, and will likely play a central role in the development of these joint preservation methods of the future. In this narrative review, we describe clinical MR image acquisition and assessment of cartilage. We discuss the semiquantitative cartilage scoring methods used in research. Lastly, we review the quantitative MRI techniques that allow assessment of changes in the biochemical composition of cartilage, even before the morphological changes are evident.
Keywords: cartilage; MRI; quantitative; semiquantitative